Kesantunan Berbahasa Dosen di Wilayah Perbatasan - Merlin Helentina Napitupulu; Thresia Trivict Semiun (Politeknik Negeri Jakarta, 2022)
This article aimed to describe the language politeness carried out by lecturers at border area of Indonesia at Timor University, especially at English Education Department. This article deals with the forms of observance of the maxims of modesty and the reasons of speech which contains of observance and non-observance maxims of language politeness. Language politeness enables lecturers to communicate better. This article is a qualitative research by using descriptive method. There were three lecturers involved as the participants in this study. The study was conducted at English Education Department of Timor University. The data collected through observation, and note taking method techniques. Data were analyzed in the following steps: (1) transcribing the recorded data into written form, (2) classifying the form of language politeness according to Leech, (3) analyzing the form of language politeness, (4) analyzing the factors of compliance and violations of language politeness, and (5) conclude the analysis results. The result shows that lecturers used both observance and non- observance maxim. Non-observance maxims were applied to give warning and motivation for the students. The lecturers’ compliance with the maxim of politeness helped the students to be more enthusiastic on learning. Based on the result, it could be concluded that it was necessary to used language politeness to make the communication could run well and effectively.